IDENTIFIKASI SALURAN PEMASARAN KOPI ARABIKA GAYO PADA CV. GAYO MANDIRI COFFEE KABUPATEN BENER MERIAH - Riyandhi Praza (LPPM Universitas Malikussaleh – Indonesia, 2017)
The high selling price of coffee paid by consumers (importers) has not been felt by farmers. The development of Gayo Arabica Coffee marketing then emerged Cooperative and CV in Bener Meriah Regency in accommodating the production of farmers one of them. CV.Gayo Mandiri Coffee (GMC) located in District Bandar, Bener Meriah Regency. CV Gayo Mandiri Coffee is engaged in Gayo Arabica coffee marketing activities. This study aims to identify the marketing channel and the Gayo Arabica coffee production process. The research was conducted using qualitative descriptive method to analyze the primary and secondary data obtained. Primary data obtained through interviews and observations, while secondary data obtained through the literature associated with this research. Gayo Arabica coffee marketing in CV.Gayo Mandiri Coffee in marketing its products there are two channels, from collectors to producers to consumers, from producers directly to consumers and from producers to retailers as well as through intermediaries then to the hands of consumers. The most dominant channels contained in CV.Gayo Mandiri is channel I because this channel is the most effective and efficient in the marketing of green bean coffee Arabica Gayo.